Challenging Disregard: Advocacy Journalism and the Campaign for Domestic Worker Legislation in Indonesia - Mary Austin (Yayasan Jurnal Perempuan, 2017)
This article examines a recent ILO funded project designed to engage more Indonesian journalists and media organizations in advocacy journalism on behalf of domestic worker legislation. Applying Ann Stoler’s notion of ‘disregard’ in the context of post-Suhartodemocratization, I illustrate how established newsroom practices and patterns of reporting helped maintain distinctions between ‘home’ and overseas domestic workers which impeded progress towards comprehensive legislation. Indonesia’s endorsement of the adoption of ILO Convention 189 in June 2011 opened up political opportunities, provided a framework for re-scripting media narratives and encouraged journalists to give more space to domestic workers’ voices. At the same time, increased media coverage enabled those opposed to legislation to reiterate a gendered disregard for the social and economic value of domestic work.